Study of quality of snacking in adolescents (12-18 years old) - Salmaani Barough N; Pashaeypour Sh; Rezaiepour A; Kazemnejad A (Tehran University of Medical Sciences, 2006)
Background & Aim: Adolescent is a unique period during the life cycle. Knowing about the suitable nutrition in this period would prevent from a lot of diseases related to the nutrition during the adulthood. But unfortunately in recent decades we have observed having unsuitable snaking in adolescents. This study aimed to determine the quality of snaking in adolescents 12-18 years old in one of district of Tehran, Iran. Methods & Materials: This study is a descriptive cross sectional research with the purpose of determining the quality of snaking in adolescents 12-18years old at 17 districts in Tehran city. The samples were 907 students that including the Iranian girls and boys who were 12-18 years old and educating in one of the guidance school or high schools of the district 17 in Tehran city. The instrument was a questionnaire and interview the data were analyzed by SPSS software. Results: The results showed that majority of students 35.1% were 14-16 years old, 52.8% were boys, 26.1% were educating in the first year of high school. 71/5% had 1-3 sisters or brothers and also the majority of students had natural BMI, 28% were having fried potato and cheese puff over than moderate level as snaking 46% were having snaking daily. Less than half of the studied cases 46.7% believe that having snaking is necessary 56.9% had sometimes snaking. Chi2 test and p<0.05 showed a significant relationship between some of demographic variables with snaking in adolescents. Conclusion: The result showed that type, time and number of snaking were not suitable and it is necessary to teach the students and their parents more about matter.